Black lives and spatial matters : policing blackness and practicing freedom in suburban St. Louis - Rios, Jodi, 1967- (Police/worlds., 2020)
"This book argues that the historical and material production of blackness-as-risk is foundational to the historical and material construction of our society and certainly foundational to the construction and experience of metropolitan space. This book also considers how an ethics of lived blackness-living fully and visibly in the face of forces intended to dehumanize and erase-can create a powerful counterpoint to blackness-as-risk"--